Optimizing Industrial Sector for Distance Learning Partnership - Kuncoro, Setyo; Thaha, Abdurrahman Rahim; Fadilla, Sarah (Journal Of Education And Teaching Learning (JETL), 2024)
The rapid advancement of knowledge in the global arena has made it imperative for universities to remain competitive. To nurture students with outstanding competencies, universities need comprehensive support from various stakeholders, especially the industrial sector. The industry sector has emerged as an indispensable collaborator, actively contributing to the educational process, particularly in distance education. The methodology used in this study includes a comprehensive literature review. The article discusses the huge role played by the industrial sector in the context of distance education and integrating experts and practitioners from the business world into the educational framework to enrich the learning process with real-world insights. In addition, providing internship opportunities for students is also considered important. Internships provide invaluable learning experiences, enhancing graduates' competencies, thus strengthening their readiness to enter the workforce. This research explores how industry involvement in education can effectively improve the quality and relevance of distance learning, ultimately producing industry-ready graduates.